Quantifying the dependence of China's water supply and regional economy on the Asian water tower - Mengdan Wei; Wei Zhang (Journal of Hydrology: Regional Studies)
Study region: The Asian water tower (AWT) encompasses the Tibetan Plateau and adjacent mountain ranges. Study focus: The AWT serves as a key water supplier for China, yet its economic role has not been adequately quantified. To address this gap, we employ a hydro-economic model to quantitatively assess the dependence of AWT water supply using a dependence index and the resulting regional economic benefits. New hydrological insights for the region: Results show that 20.64 ± 0.26 % of China's water demand is met by the AWT, of which 97.43 % ± 0.04 % flows to six provinces. From 2012–2017, this supply remained stable, contributing 2.57 ± 0.30 % to value added via trade networks, and up to 13.11 ± 0.49 % when excluding regional heterogeneities. The primary beneficiaries include Sichuan (37.13 ± 0.19 %), Tibet (38.51 ± 0.01 %), Qinghai (34.98 ± 0.00 %), Xinjiang (23.59 ± 2.00 %), Gansu (17.20 ± 1.04 %) and Ningxia (14.83 ± 0.84 %), all characterized by high AWT dependency. These provinces have realized substantial economic gains in high-value sectors and water-intensive industries. In high-altitude areas, agriculture remains essential; in arid regions, tap water production sustains local economies. Furthermore, reductions in AWT water supply would disproportionately affect underdeveloped provinces. Our findings reveal the AWT's role beyond hydrology, reflecting provinces whose value added may benefit from AWT water supply even if their reliance on its resources is not.